The Effect Of Arm Muscle Strength On Throw-In Ability In Football Games In Elementary School Students - Astuti, Tiara Nuarasyifa; Sudirjo, Encep; Saptani, Entan (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of arm muscle strength on the ability to throw in football in elementary school students. This study uses a Quantitative method with a Pre-experimental approach and uses a Group Pre-test and Post-test Design research design to determine the differences before and after being given certain treatments. The population in this study was students of SDN Bunter 1 in grades III, IV, and V who participated in extracurricular football, with a sample of 20 people. Data collection techniques used tests and measurements, while data analysis was carried out using t-test statistics. Using a throw test as an instrument in the study. This study found that the average score of the final throw test was higher than the initial test. The conclusion shows that arm muscle strength affects the ability to throw in football in elementary school students at Bunter 1, located in Cimanggung District, Sumedang Regency.